The reciprocal relation between rising longevity and temperature-related mortality risk in older people, Spain 1980–2018 - Simon J LLOYD; Erich STRIESSNIG; José Manuel ABURTO; Hicham ACHEBAK; Shakoor HAJAT; Raya MUTTARAK; Marcos QUIJAL-ZAMORANO; Constanza VIELMA; Joan BALLESTER (Environment International)
Temperature-related mortality mostly affects older people and is attributable to a combination of factors. We focussed on a key non-temperature factor – rising longevity – and aimed to quantify its reciprocal relation with temperature-related mortality risk in Spain over 1980–2018.We obtained average annual temperature-attributable deaths among people aged 65y+, by sex and age group, for different temperature ranges (extreme cold, moderate cold, moderate heat, and extreme heat), from a previous study. Combining this with population and mortality data as well as life table information, we used: (i) a counterfactual approach to assess the contribution of rising longevity to changes in the absolute risk of temperature-related mortality, and (ii) decomposition to assess the contribution of changes in temperature-related mortality to changes in longevity and its variation (lifespan inequality).Rising longevity led to considerable declines in the absolute risk of temperature-related mortality in females and males across the entire temperature range. For extreme heat, it accounted for about a 30% decrease in absolute risk (half of the total decrease over the study period). For moderate and extreme cold, it accounted for about a 20% fall in absolute risk (a quarter of the total fall). In the opposite direction, changing patterns of temperature-related deaths contributed to higher life expectancy (accounting for > 20% of the total rise in both females and males) but also higher lifespan inequality amongst older people. Most of the influence (about 80%) was via moderate cold, but declines in risk at both moderate and extreme heat led to small rises in life expectancy.Our study points to the benefits of adopting risk-reduction strategies that aim, not only at modifying hazards and reducing exposure, but that also address socially-generated vulnerability among older people. This includes ensuring that lifespans lengthen primarily through increases in years lived in good health.